2020
DOI: 10.1038/s41597-020-0401-2
|View full text |Cite
|
Sign up to set email alerts
|

Fox Insight collects online, longitudinal patient-reported outcomes and genetic data on Parkinson’s disease

Abstract: Fox Insight is an online, longitudinal health study of people with and without Parkinson’s disease with targeted enrollment set to at least 125,000 individuals. Fox Insight data is a rich data set facilitating discovery, validation, and reproducibility in Parkinson’s disease research. The dataset is generated through routine longitudinal assessments (health and medical questionnaires evaluated at regular cycles), one-time questionnaires about environmental exposure and healthcare preferences, and genetic data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 10 publications
0
80
0
Order By: Relevance
“…Fox Insight (FI) is a fully remote study platform [ 12 ]. Participants ≥18 years old with and without PD complete surveys at regular intervals and are periodically invited to complete additional surveys targeting particular topics [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fox Insight (FI) is a fully remote study platform [ 12 ]. Participants ≥18 years old with and without PD complete surveys at regular intervals and are periodically invited to complete additional surveys targeting particular topics [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several PD-related genes may be pertinent to COVID-19 infection: LRRK2 mutations may play a role in immunomodulation [ 13 ], while APOE ɛ 4 homozygosity has been associated with increased COVID-19 risk [ 14 ] and, along with GBA, may increase susceptibility to cognitive impairment in people with PD [ 15 ]. Genotype was therefore included for the subset of people with PD in FI who had those data available [ 11 ]. Information about PD diagnosis was obtained both from FI and from our current survey; respondents with conflicting answers were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We submitted our online survey to all eligible participants of Fox Insight, which is sponsored by The Michael J. Fox Foundation for Parkinson’s Research 52 . Participants affirmed an online statement of informed consent prior to the study, explaining the nature and length of the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were recruited through the Fox Insight (FI) study. Fox Insight study methods have been described elsewhere in detail ( 12 ). Briefly, FI is an online-only longitudinal observational study in which individuals with and without self-reported PD participate in study activities via an online platform.…”
Section: Methodsmentioning
confidence: 99%